Application of ant colony algorithm in the simulationbased approach to improve airport surface operations. (2015) - Wei, Wenbin; Davis, Lawrence; Fu, Chunsheng; Ding, Yanan
In this paper, we apply the ant colony algorithm in the optimiser for the simulationbased optimisation approach to improve airport surface operations. The major components of the system architecture and detailed descriptions of the implementations of the ant colony algorithm are introduced. The proposed ant colony algorithm and the simulationbased optimisation approach are applied to the case studies of the east side of the DallasFort Worth airport (DFW). The initial results have demonstrated the success and benefit of applying the ant colony algorithm in the simulationbased approach for improving airport surface operations. The results have also implied that applying the combined genetic algorithm and ant colony algorithm in the optimiser can derive better results than using any one of the two algorithms solely.